2012
DOI: 10.1186/1754-9493-6-8
|View full text |Cite
|
Sign up to set email alerts
|

Description of a multicenter safety checklist for intraoperative hemorrhage control while clamped during robotic partial nephrectomy

Abstract: BackgroundThe adoption of robotic assistance has contributed to the increased utilization of partial nephrectomy for the management of renal tumors. However, partial nephrectomy can be technically challenging because of intraoperative hemorrhage, which limits the ability to identify the tumor margin and may necessitate the conversion to open surgery or radical nephrectomy. To our knowledge, a comprehensive safety checklist does not exist to guide surgeons on the management of hemorrhage during robotic partial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…Direct pressure is immediately applied and the insufflation pressure increased while the renorrhaphy clips are re-tightened. Emergent open conversion or conversion to robotic total nephrectomy may be necessary for uncontrolled bleeding (Nepple et al, 2012). …”
Section: Complicationsmentioning
confidence: 99%
“…Direct pressure is immediately applied and the insufflation pressure increased while the renorrhaphy clips are re-tightened. Emergent open conversion or conversion to robotic total nephrectomy may be necessary for uncontrolled bleeding (Nepple et al, 2012). …”
Section: Complicationsmentioning
confidence: 99%
“…A Satinsky clamp could be a backup option for hilar clamping if the renal hilar vessels are difficult to identify for clamping of individual vessels with bulldog clamps or if there are dense adhesions around the hilum that could increase the risk of vascular injury with further dissection. If bulldog clamps were to ''fail'' with bleeding from the resection bed in spite of bulldog placement, the Satinsky clamp could provide a backup option to definitively ''shut down'' blood flow to the kidney after other hemostatic maneuvers have failed [8]. The Satinsky clamp also provides a relatively easy way to ''flash'' the clamp and to quickly open the clamp to minimize warm ischemia time, such as in the cases of early unclamping [9].…”
Section: Discussionmentioning
confidence: 99%
“…suggested that once the mass is excised, further hemostatic measures can be carried out, including cauterizing the base of the resection bed, suturing the resection bed and placing sliding clip renorrhaphy sutures, which ultimately provides compression of the parenchyma. However, if bleeding is not manageable, emergent open conversion (OPN or complete nephrectomy) or robotic nephrectomy might be necessary …”
Section: Ebl and Intraoperative Hemorrhagementioning
confidence: 99%
“…Our preference is to only clamp the renal artery even with hilar lesions. If bleeding is encountered during resection, management is based on whether the bleeding is suspected to be arterial or from venous back bleeding . Today, it is believed that the only reliable hemostasis is the suture.…”
Section: Ebl and Intraoperative Hemorrhagementioning
confidence: 99%